Prevalence and Clinicopathological Features of Autoimmune Pancreatitis in Japanese Patients With Inflammatory Bowel Disease. Issue 3 (April 2015) - Ueki, Toshiharu; Kawamoto, Kenichiro; Otsuka, Yuichiro; Minoda, Ryohei; Maruo, Toru; Matsumura, Keiichiro; Noma, Eijiro; Mitsuyasu, Tomoko; Otani, Keisuke; Aomi, Yoshiaki; Yano, Yutaka; Hisabe, Takashi; et al.
Abstract : Objectives: The purpose of this study was to clarify the clinicopathological characteristics of autoimmune pancreatitis (AIP) in Japanese patients with inflammatory bowel disease (IBD). Methods: The clinicopathological findings of 7 patients with IBD whose definite AIP was diagnosed in our hospital according to the International Consensus Diagnostic Criteria were reviewed. Results: Five (0.5%) of 961 patients with ulcerative colitis (UC) and 2 (0.3%) of 790 patients with Crohn disease had AIP. All of 7 patients whose AIP was diagnosed were type 2. The rate of elevated values of serum immunoglobulin G4 was 0%. Most patients with the diagnosis of IBD preceded that of AIP, and disease activity of IBD were active. Granulocyte epithelial lesion is similar to the cryptitis seen in colonic tissue of UC. All of 7 patients were given corticosteroids, immunomodulators, and/or biological agents for IBD. One patient had a recurrence. Conclusions: The frequency of AIP in Japanese patients with IBD was low. All cases were type 2 and responded well to corticosteroids, immunomodulators, and biological agents. Autoimmune pancreatitis in UC patients may be an extraintestinal manifestation of UC.